Exploring Job Crafting Among State Civil Apparatus: A Descriptive Qualitative Study - Khansa, Indri Hapsari; Izzati, Umi Anugerah (Indonesia Banking School, 2025)
This study analyzes job crafting practices among civil servants at the Department of Manpower and Transmigration of East Java Province (Disnakertrans Jatim). Using a qualitative descriptive design, data were collected through in-depth interviews with five purposively selected employees. Thematic analysis reveals that employees engage in all three dimensions of job crafting, though the extent of implementation varies. Relational crafting emerged as the most dominant dimension for strengthening social capital and work coordination. Cognitive crafting is utilized by employees to redefine the meaning of their work, while task crafting remains limited to informal adjustments due to bureaucratic constraints. These findings underscore that job crafting serves as a crucial mechanism for employee adaptability in the public sector. Practically, this study recommends the need for flexible organizational structures, increased autonomy, and enhanced inter-unit collaboration to optimize public service performance.